INTERLEUKIN-40 AS A PREDICTIVE TOOL OF RESPONSE TO TREATMENT FOR INSULIN RESISTANCE IN PATIENTS WITH TYPE 2 DIABETES (CAHIERS MAGELLANES-NS, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a prevalent chronic metabolic disorder primarily characterized by impaired insulin secretion from pancreatic β-cells or insulin receptor dysfunction. Both defects are linked to dysregulated cytokine production. A complex interplay between pro-inflammatory and anti-inflammatory cytokines is hypothesized to contribute to T2DM development and its complications. The present investigation sought to establish a novel biochemical association between IL-40 and type 2 diabetes mellitus (T2DM) and to assess IL-40 levels in serum samples obtained from T2DM patients and healthy controls. Materials and Methods: A study involving 90 participants investigated the levels of interleukin-40 in the blood. The participants were divided into two main groups: patients with a condition and healthy individuals: The patient group was further divided into three subgroups: Group 1 (G1) consisted of 20 patients (equal numbers of males and females) receiving only insulin-deficient medications. Group 2 (G2) included 20 patients (balanced male and female representation) who were treated with both insulin-deficient medications and medications to lower insulin resistance. Group 3 (G3) comprised 30 patients (15 males and 15 females) who solely received insulin resistance-lowering medications. The healthy control group included 20 individuals (10 males and 10 females) between 30 and 60 years of age who showed no signs of the condition. A technique called Sandwich-ELISA was used to measure the amount of interleukin-40 in the blood samples collected from all participants. Results: The study shows that there is significant statistical difference (p=0.000) in interleukin-40 levels when comparing the group of type 2 Diabetes disease patients to the healthy group. Statistically significant differences were observed in interleukin-40 levels between diabetic patients treated exclusively with insulin deficiency medications, the group of patients taking medications to improve insulin resistance with treatment for insulin deficiency (p=0.008) and the third group of patients taking medications to improve insulin resistance only (p=0.043). In addition, statistical discrepancies in interleukin 40 levels were identified between group 1 and healthy controls (p=0.022). the study identified no significant variations in interleukin 40 levels between males and females within each group (healthy individuals or diabetics). The only exception was the second group of patients who were administered both insulin deficiency drugs and medications to improve insulin resistance. In this particular group, a significant difference in interleukin 40 levels between the sexes was observed (P=0.003).The same trend holds true for comparisons between females within the type 2 diabetes (T2DM) groups, with one exception. Within the T2DM group, females in (G1) had significantly higher interleukin-40 levels compared to females in (G2) and  (G3). This difference was also observed when compared to the healthy control group. Statistically significant differences were found between G1 females and G3 females (p=0.015), between G1 females and G5 females (p=0.000), and between G1 females and the control group (p=0.000). “Similarly, no significant difference in interleukin-40 levels was observed when comparing males within T2DM and with control groups. However, interleukin-40 levels in G2 males were significantly higher compared to males in G4 (p=0.000), and males in G6 (p=0.000) And the males in the control group (G8), (p=0.003). Conclusions.Interleukin-40 is a good parameter for evaluating the T2DM patients respond to treatment in the three disease groups, regardless of the type of treatment used